Tingkat Keberhasilan Kawasan Semarang Bridge Fountain sebagai Ruang Publik Perkotaan - Dwi Aji Darmawan; Hadi Wahyono (Teknik PWK (Perencanaan Wilayah Kota), 2019)
The Semarang Bridge Fountain area is one of the public spaces in Semarang City. The area became a new public space which was inaugurated on December 31st, 2018. The public space was provided by the Semarang City Government to meet the needs for public space in Semarang City. The existence of the Semarang Bridge Fountain Area aims as a new icon of Semarang City that provides a new activity space for the community. The existence of the public space is expected to be a gathering space for the people of Semarang. The public space can also be used as recreation or just to enjoy the atmosphere in Semarang City, In fact there are some problems that exist in the public space, such as traffic jams on regional roads, damage to the supporting facilities provided. Of the several existing problems, the success rate of the existing public space is measured, the Semarang Bridge Fountain as a new public space in providing activity space. The success rate is measured based on the conditions of the availability of supporting facilities and user activity in the region. The results of this measurement show the success rate of the Semarang Bridge Fountain area into the good category, and good for public space in Semarang City.